When You See Us, See Us: Black Girl Futurity and Liberation. Issue 3 (1st December 2022) - Unknown
Abstract : Battle, Nishaun. Black Girlhood, Punishment, and Resistance: Reimagining Justice for Black Girls in Virginia. New York: Routledge, 2020.